SIFAT ORGANOLEPTIK PADA MIE BASAH DENGAN SUBSITUSI TEPUNG IKAN KEMBUNG (RASTRELLIGER SP.) DAN TEPUNG DAUN KELOR (MORINAGA OLEIFERA L.) - Anna Sarmpumpwain; Rosita Antariksawati (ITB AAS INDONESIA Surakarta, 2022)
Noodles are a type of food favored by all people and are often used as a substitute for rice. The nutritional content of protein in noodle products is very low, so it is necessary to add a high protein composition such as mackerel and vitamins derived from Moringa leaf vegetables which are high in vitamin A, which aims to increase the nutritional value of wet noodles, in order to determine the nutritional content of this innovation, it is important conducted a study on the organopleptic properties of wet noodles with the substitution of mackerel fish meal (Rastrelliger sp.) and Moringa leaf flour (Moringa oleifera L.)”. This research is a quasi-experimental research conducted in a laboratory. The design used is One Shot Case Study, and analyzed with SPSS 20 to determine the average percentage of each parameter and narrated descriptively. Based on the organoleptic test conducted on the same 20 panelists for 2 days, from the three formulas of wet noodles with the substitution of mackerel fish meal and Moringa leaf flour, the results for the color of the formula that were most favored by the panelists were F2 as much as 55% stated sua. The most preferred aroma by the panelists was F2 as much as 62.5% said they liked it. The taste that the panelists most liked was F1 as much as 47.5% said they liked it, and the texture that the panelists liked the most was F2 as much as 45% said they liked it. The conclusion of this study shows that wet noodles with the substitution of mackerel flour and Moringa leaf flour can add nutritional value such as macro nutrition, namely Energy, Protein, Fat, and Carbohydrates.